MODERASI ISLAM DALAM KESETARAAN GENDER (KOMPARASI TERHADAP AGAMA YAHUDI DAN NASRANI) - Meirison, Meirison; Saharuddin, Desmadi; Rosdialena, Rosdialena; Ridho, Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Islam is a moderate religion that is very close to the dignity of women which is very different from the two religions of its predecessors. In both religions women are considered as a burden in life and very detrimental, women's rights are morally and materially ignored. Like ownership of property, the right to issue testimony, identity is assigned to the husband not to his father. Even as far back as 1956 and perhaps up to now in France and Germany full of women's freedom must obtain the husband's permission to conduct transactions, such as buying and selling, grants from his own property. With library studies and comparative approaches and qualitative methods the author reveals whether Jews and Christians have similarities in their treatment of women in theory and is there a difference between the two religions? Do Islam, Judaism and Christianity in theory give equal treatment to women? Let a Muslim know that there is a gap between the teachings of Islam and the behavior of some Muslims today that are no longer in accordance with Islamic norms. Such behavior does not originate from Islam as a moderate religion.Keywords: Islamic Moderation, In Gender, Comparison, Judaism and Christian.